Family and Business Financial Planning Training in the Community T. Kolam A. Yarang Ch. Pattani, Thailand - Ayuningtyas, Rosida Dwi; Yurista, Dina Yustisi; Sari, Risti Lia; Astuti, Wulan Budi; Ariyanti, Yulekhah; Buenae, Hasan (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2024)
One of the efforts to improve the quality of human resources on the economic and financial side is to provide improved community skills so that they are expected to get decent jobs and can get better income. Before carrying out the activity, some preparations were made. Preparation includes discussion of setting goals to be achieved, forms of activities and target participants. The discussion agreed on the form of activities was training on family financial management and Business Management. This training event was approximately 20 participants. In the Family Financial Planning Training activity, there were 15 participants, of which 80% were housewives / workers and 20% were men. Of the 15 participants, 75% were able to use financial management applications because age and feature retention were the main factors that caused them to be able to, the rest could only but had to look at the records of the stages Participants have been able to identify needs and wants due to limited financial income so strategies are needed to increase participants' income, one of which is online business.